Aerodynamics of Harmonically Oscillating Aerofoil at Low Reynolds Number - Rahman,Aiman Hakim Abdul (2017)
ABSTRACT: Two-dimensional flows over harmonically oscillating symmetrical aerofoil at reduced frequency of 0.1 were investigated for a Reynolds number of 135,000, with focus on the unsteady aerodynamic forces, pressure and vortex dynamics at post-stall angles of attack. Numerical simulations using ANSYS® FLUENT CFD solver, validated by wind tunnel experiment, were performed to study the method of sliding mesh employed to control the wing oscillation. The transport of flow was solved using incompressible, unsteady Reynolds-Averaged Navier-Stokes equations. The 2-equation k-ε realizable turbulence model was used as turbulence closure. At large angle of attack, complex flows structure developed on the upper surface of the aerofoil induced vortex shedding from the activity of separated flows and interaction of the leading edge vortex with the trailing edge one. This interaction at some stage promotes the generation of lift force and delays the static stall. In this investigation, it was found that the sliding mesh method combined with the k-ε realizable turbulence model provides better aerodynamic loads predictions compared to the methods reported in literature.